Participação dos gestores no planejamento estratégico: um estudo envolvendo os setores de alimentos, química e petroquímica e, metalurgia e siderurgia - Lautert, Juliano (Universidade do Vale do Rio do Sinos, 2009)
This research has found if there is the involvement of the managers in the strategic planning process, establishing the strategic planning process in three stages: planning, carry out and control, and besides, the stages of implementation and control with focus in the budget analysis. The study was based on identification of lack of research that pointed, at all stages, the managers’ involvement in the process, even though participatory. To achieve the general purpose, that was identify if there is the managers’ involvement in the strategic planning process , a survey was performed, with a questionnaire of closed questions, and that was scored in a scale adapted from Likert’s scale. This questionnaire was send to controllers of 190 companies listed in the magazine Valor 1.000, edition 2.008. To analyze the information, object in the questionnaire, they were organized in groups, so which group indicated the manager involvement in which process stage, with the follow results: Group 2: Managers’ involvement lev
Keywords: controle; execução; planejamento; carry out; control; planning; Ciências Sociais Aplicadas